The Ombudsmen: Time for Jurisdictional Expansion The Case for Extending the Jurisdiction of The Statutory Ombudsmen to Cover the Exercise of Public Power in the Private Sector - Cameron, Alistair (Victoria University of Wellington Law Review, 2001)
The diffusion of public power in New Zealand through state sector reforms is well documented. As "public functions" are increasingly exercised by "private" bodies other than the traditional array of Ministries and Departments, the questions arise as to whether the "public law" tools that have historically accompanied such exercise continue to apply. This article argues that one such "tool", the Ombudsman, is particularly suited to application in the control of the exerciseof public power by the private sector. In doing so, the author traverses the arguments made for extending the application of public law tools to the private sector, the extent to which public laws have so far been applied to private sector exercises of public power, and the particular reasons for extension of the jurisdiction of the Ombudsmen thereto.